Karakteristik Batugamping Daerah Pilobuhuta Dan Sekitarnya, Kecamatan Batudaa Kabupaten Gorontalo - Atima, Karina Febriani K.; Permana, Aang Panji; Hutagalung, Ronal (Journal of Applied Geoscience and Engineering, 2025)
Administratively, the research location is in Pilobuhuta Village, Batudaa District, Gorontalo Regency, with an area of 4.8 KM². Limestone is a sedimentary rock formed from calcium carbonate deposits. These rocks are often found in various areas, including in Pilobuhuta Village, Batudaa District, Gorontalo Regency. The Pilobuhuta area has unique geological conditions, with hills that have the potential to be a location for limestone formation. Research on the characteristics of limestone in this area to identify the mineral composition, structure, and texture of existing rocks, as well as to determine the porosity value of limestone in this area. The aim of this research is to map the geological conditions of the Pilobuhuta area and its surroundings, analyze the characteristics of limestone, and analyze the porosity value of limestone in the research area. The research method used is surface geological mapping and porosity analysis in the form of petrographic analysis and specific gravity analysis. The research results show that the research area consists of four limestone facies units, namely mudstone facies, wackestone facies, packstone facies, and grainstone facies. The geomorphological units in this area are divided into two land forms, namely alluvial lowland units and denudational hills. The porosity value of the limestone in the research area ranges from fair to very good. The porosity value in the mudstone facies is in the fair category, the wackestone facies is in the good category, the packstone facies is in the very good category, and the grainstone facies is in the fair category.